2006
DOI: 10.1007/s00395-005-0580-1
|View full text |Cite
|
Sign up to set email alerts
|

Protection against myocardial ischaemia/reperfusion injury by PPAR–α activation is related to production of nitric oxide and endothelin–1

Abstract: The results suggest that the PPAR-alpha activation protects the rat myocardium against ischaemia/ reperfusion injury via a mechanism related to production of NO, and possibly ET-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 34 publications
2
41
0
2
Order By: Relevance
“…2B). It is interesting that treatment of ischemic rats with a PPAR-␣ ligand has been shown to be cardioprotective as a result of nitric oxide production (Bulhak et al, 2006), which has also been shown to repress Cyp1a2 mRNA (Mulero-Navarro et al, 2003). Although definitive proof is still lacking, these findings and the observations in Fig.…”
Section: Discussionmentioning
confidence: 80%
“…2B). It is interesting that treatment of ischemic rats with a PPAR-␣ ligand has been shown to be cardioprotective as a result of nitric oxide production (Bulhak et al, 2006), which has also been shown to repress Cyp1a2 mRNA (Mulero-Navarro et al, 2003). Although definitive proof is still lacking, these findings and the observations in Fig.…”
Section: Discussionmentioning
confidence: 80%
“…At the same time, NOS actions might play a protective role against inflammatory injury by mature leukocytes which have been recently been described in the cremaster muscle 36 and in ischemia and reperfusion injury to the heart. 37 NOS might be a determinant for tissue to decide about the amount of inflammation and regeneration.…”
Section: Stem Cell Adhesion Requires Enosmentioning
confidence: 99%
“…All treatments were given as intravenous injections 30 min before coronary artery occlusion. The dose of WY, L-NNA, and wortmannin (Sigma, St. Louis, MO) and the concentration of DMSO were based on previous studies of myocardial ischemia-reperfusion injury (5,28,36).…”
mentioning
confidence: 99%